Food Preservation and Waste Exploitation - Socaci, Sonia A.; F?rca?, Anca C.; Aussenac, Thierry; Laguerre, Jean-Claude (IntechOpen, 2020)
One of the biggest challenges facing the food industry and society is the reduction of food waste. Annually, all over the world, millions of tons of agro-food waste are produced, and their efficient management and valorization represents one of the main objectives of EU actions towards sustainable development. The book compiles information on the possibilities of the recovery of valuable compounds from food waste and their valorization in different food and non-food applications, as well as new preservation methods for optimizing food waste reduction.